Clinical manifestations of neuroborreliosis in children – review of literature - Ćwik-Błotnicka, Dominika; Bieńko, Karolina; Białek, Justyna; Borczyk, Joanna; Więckowska-Deroń, Marta; Leszcz, Monika (Journal of Education, Health and Sport, 2023)
Introduction: The most common tick-borne disease caused by the spirochete Borrelia burgdorferi is Lyme disease. It is characterized by a variety of disorders: dermatological, rheumatological, cardiological and neurological. Neuroborreliosis is defined as an involvement of the nervous system, and it is the second most common form of infection in children (10-15% of those infected). The aim of the study: To review the available materials and presentation of the current state of knowledge on the various manifestations of neuroborreliosis in children. Material and method: Databases such as PubMed and Google Scholar were searched. Literature was searched using the keywords: Lyme disease, neuroborreliosis, borreliosis, facial nerve paralysis, and pediatric population. The materials obtained in this way were analyzed in terms of compliance with the subject of the work. Results: Typical clinical manifestations of neuroborreliosis in children are facial nerve palsy and meningitis. Neuroborreliosis is the cause of 50% of all cases of bilateral facial nerve palsy in children. Multiple cranial and peripheral neuritis, myelitis, cerebral vasculitis and, consequently, the formation of intracranial aneurysms are less common manifestations of infection. Conclusions: The symptoms of neuroborreliosis are non-specific. This makes it difficult to make an accurate diagnosis. Even if no information on tick bite or erythema migrans has been obtained from the clinical history, neuroborreliosis should be considered in the differential diagnosis, especially in Lyme-endemic areas.